2005
DOI: 10.1200/jco.2005.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Minimal Residual Disease in B-Cell Chronic Lymphocytic Leukemia After Alemtuzumab Therapy Is Associated With Prolonged Survival

Abstract: MRD-negative remission in CLL is achievable with alemtuzumab, leading to an improved overall and treatment-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
264
2
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(282 citation statements)
references
References 25 publications
11
264
2
5
Order By: Relevance
“…Importantly, several studies have shown that infectious events typically occur around the time of T-cell and neutrophil nadirs (Fig. 1) [13,30,38,40,49].…”
Section: Effect Of Alemtuzumab On Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, several studies have shown that infectious events typically occur around the time of T-cell and neutrophil nadirs (Fig. 1) [13,30,38,40,49].…”
Section: Effect Of Alemtuzumab On Immune Cellsmentioning
confidence: 99%
“…Similarly, in the pivotal study of 93 relapsed/refractory CLL patients, 25 patients (27%) experienced grade 3/4 infectious events (27%), which occurred more frequently in non-responders than in responders (36% versus 9.7%) [30]. In a recent study, 91 patients with relapsed/refractory CLL were treated with alemtuzumab until maximum response, which included achievement of minimal residual disease (MRD)-negative remission [38]. There were four infectious episodes in 18 MRD-negative patients, compared with 27 episodes in 73 patients who did not achieve MRD negativity.…”
Section: Infectious Events Associated With Alemtuzumab Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment regimens with purine nucleoside analogues and monoclonal antibodies (mAb) have increased the rate of molecular complete remissions and may result in a longer time to progression. [1][2][3] However, these options bear significant risks for infectious complications, which must be carefully weighted against the risks by the underlying disease. 4,5 Allogeneic hematopoietic cell transplantation (HCT) is the only potentially curative therapy for B-CLL, 6,7 but due to the high treatment-related mortality and advanced age of most patients, the procedure is not applicable for the majority of B-CLL patients.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that fludarabine and alemtuzumab improved response rates compared with traditional alkylating agents but also caused significant immunosuppression. 11,12 Autologous and allogeneic hematopoietic cell transplantation (HCT) also are associated with prolonged neutropenia and immunosuppression, which results in fungal, viral, and other opportunistic infections. 13,14 The objective of the current study was to assess the relations between new prognostic markers and therapies on the type of infections encountered, the time taken to develop these infections, and the infection-related mortality (IRM) rate.…”
mentioning
confidence: 99%